Entre o local e o global: reflexões sobre o currículo de formação em animação turística da ESHTI/Moçambique - Gustavo Schünemann Christófaro Silva (2023)
The doctoral research aimed to investigate the formation of the Bachelor's Degree in Tourism Animation at ESHTI, with a focus on the organization of its curriculum elements. To achieve this, the goal was to identify and understand the structure of the curriculum knowledge that comprises the program, analyzing the involvement of actors in curriculum development and the power dynamics that influence curriculum decisions. Additionally, the research sought to comprehend how the curriculum relates to the sociopolitical and economic needs of the context in which it operates. The methodology employed included bibliographic, documentary, and field research. The bibliographic research involved reviewing studies related to topics such as curriculum, (de)coloniality, post-colonialism, African studies, and professional training in leisure and tourism. The documentary research focused on documents such as the Graduation Curriculum Framework of UEM, the curriculum matrix of ESHTI's offered courses, the institution's internal regulations, and its financial activity reports. Field research was conducted at ESHTI in Inhambane, Mozambique, through semi-structured interviews with institution faculty. The conclusions highlight that, despite the region of Inhambane having significant global tourism potential, the training in Tourism Animation at ESHTI faces challenges. There appears to be a dichotomy between theory and practice in the institution's approach, and the strong emphasis on market demand may limit the development of broader skills in students. Additionally, the research reveals concerns about the underrepresentation of women in the faculty, the influence of colonialism on educational and power structures, and the reliance on curricula from other institutions. These issues point to the need to rethink Tourism Animation education, promoting a more inclusive and culturally sensitive approach. The research also emphasizes the importance of reimagining the school curriculum, questioning the hegemony of Eurocentric knowledge and fostering pedagogical practices that consider cultural diversity and interculturality. The research proposes a curriculum approach that values local knowledge and challenges colonial structures of power and knowledge.